How Science-Mathematics based Fairytale Book Enhance Critical Thinking Skills and Curiosity in Elementary School Students? - Nur Luthfi Rizqa Herianingtyas; Tri Suryaningsih; Mohamad Syarif Sumantri; Erry Utomo; Nina Nurhasanah (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThis study aims to develop a fairytale book based on Science-Mathematics suitable to enhance critical thinking skills and curiosity and reveal the effectiveness of the fairytale book based on Science-Mathematics to improve critical thinking skills and curiosity. Moreover, this study was conducted at two State Elementary Schools in Yogyakarta, Indonesia. This study employed the R & D method adapted by Borg and Gall consisting of 10 steps, including (1) collecting information, (2) planning, (3) developing a preliminary xform of product, (4) conducting preliminary field testing, (5) revising main product, (6) conducting main field testing, (7) revising operational product, (8) conducting operational field testing, (9) revising final product, and (10) conducting dissemination and implementation. Moreover, the data were collected through interviews (need analysis), tests, observations, and questionnaires. Before data collection, the productsâ€™ validation was conducted by involving learning media experts, material experts, linguist experts, and teachers and students. After that, data were analysed using a MANOVA test with a significance level of 5%. The result showed that the Science-Mathematics-based fairytale book was feasible based on learning media, material, and linguist experts with a predicate of â€œvery goodâ€. Additionally, the Science-Mathematics-based fairytale book effectively improved critical thinking skills and curiosity with medium effectiveness.Keywords: fairytale, critical thinking, curiosityÂ AbstrakPenelitian ini bertujuan untuk mengembangkan buku dongeng berbasis Sains-Matematika yang sesuai untuk meningkatkan kemampuan berpikir kritis dan rasa ingin tahu serta mengetahui keefektifan buku dongeng berbasis Sains-Matematika untuk meningkatkan kemampuan berpikir kritis dan rasa ingin tahu. Selain itu, penelitian ini dilakukan di dua Sekolah Dasar Negeri di Yogyakarta, Indonesia. Penelitian ini menggunakan metode R & D yang diadaptasi dari Borg dan Gall, yang terdiri dari 10 langkah, yaitu (1) mengumpulkan informasi, (2) melakukan perencanaan, (3) mengembangkan produk awal, (4) melakukan uji coba lapangan awal, (5) merevisi produk utama, (6) melakukan uji coba lapangan utama, (7) merevisi produk operasional, (8) melakukan uji coba lapangan operasional, (9) merevisi produk akhir, dan (10) melakukan diseminasi dan implementasi. Selain itu, data dikumpulkan melalui wawancara (analisis kebutuhan), tes, observasi, dan kuesioner. Sebelum pengumpulan data, dilakukan validasi produk dengan melibatkan ahli media pembelajaran, ahli materi, ahli bahasa, serta guru dan siswa. Setelah itu, data dianalisis menggunakan uji MANOVA dengan taraf signifikansi 5%. Hasil penelitian menunjukkan bahwa buku dongeng berbasis Sains-Matematika layak berdasarkan ahli media pembelajaran, ahli materi, dan ahli bahasa dengan predikat â€œsangat baikâ€. Selain itu, buku dongeng berbasis Sains-Matematika efektif meningkatkan kemampuan berpikir kritis dan rasa ingin tahu dengan tingkat keefektifan sedang.Kata kunci: dongeng, berpikir kritis, rasa ingin tahu